Crossmodal facilitation of masked visual target identification. - Ngo, M; Spence, C (2010)
In the present study, participants identified the location of a visual target presented in a rapidly masked, changing sequence of visual distractors. In Experiment 1, we examined performance when a high tone, embedded in a sequence of low tones, was presented in synchrony with the visual target and observed that the high tone improved visual target identification, relative to a condition in which a low tone was synchronized with the visual target, thus replicating Vroomen and de Gelder's (2000, Experiment 1) findings. In subsequent experiments, we presented a single visual, auditory, vibrotactile, or combined audiotactile cue with the visual target and found similar improvements in participants' performance regardless of cue type. These results suggest that crossmodal perceptual organization may account for only a part of the improvement in participants' visual target identification performance reported in Vroomen and de Gelder's original study. Moreover, in contrast with many previous crossmodal cuing studies, our results also suggest that visual cues can enhance visual target identification performance. Alternative accounts for these results are discussed in terms of enhanced saliency, the presence of a temporal marker, and attentional capture by oddball stimuli as potential explanations for the observed performance benefits.